Rationalization of running techniques based on coordinated movements of all link of the flying leg - Mironov A.A.; Kiryanova L.A.; Morozova L.V.; Lyashenko O.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to formulate and practically justify the concept of running technique, taking into account the interaction of coordinated movements of all parts of the fly leg when performing a running step. Methods and structure of the study. The pedagogical experiment was carried out during the summer training camp with highly qualified athletes in athletics (age 23,5 ± 0,7 years), who were divided into 8 people into two comparison groups: experimental and control. In the course of the work, the basic principles of the concept of running technique were formulated and two sets of exercises were developed that have an effective impact on the running step technique in the running disciplines of multi-athletes. Results and conclusions. According to the provisions of the concept of running technique, taking into account the interaction of coordinated movements of all parts of the swing leg when performing a running step and the developed sets of exercises, the results of the pedagogical experiment recorded positive dynamics: when running 100 m, the results improved by 10,7%; at a distance of 200 m – by 10,5%; times at distances of 600 and 400 m became higher by more than 10%. As a result of the work, it was established that the lack of the vertical component of the ground reaction force impulse is an external factor limiting running speed; when running along a distance, the resulting direction of take-off is close to vertical; forward acceleration of all links of the swing leg throughout the entire period of support allows you to increase the moment of force of moving the free leg forward.